2008
DOI: 10.1097/tp.0b013e31818a81b2
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Magnetic Nanocarriers for Image-Tagged SiRNA Delivery to Intact Pancreatic Islets

Abstract: Background With the ultimate hope of finding a cure for diabetes, researches are looking into altering the genetic profile of the beta cell as a way to manage metabolic dysregulation. One of the most powerful new approaches for the directed regulation of gene expression utilizes the phenomenon of RNA interference. Methods Here, we establish the feasibility of a novel technology centered around multifunctional magnetic nanocarriers, which concurrently deliver siRNA to intact pancreatic islets and can be detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Green fluorescent protein (GFP)-targeting siRNA (siGFP, sense: 5’-CAAGCUGACCCUGAAGUUdTdT-3’; antisense: 5’-GAACUUCAGGGUCAGCUUdTdT-3’) 22 and fluorophore-labeled negative control siRNA (siDY547, sense: 5’-DY547-UUCUCCGAACGUGUCACGUdTdT-3’; antisense: 5’-ACGUGACACGUUCGGAGAAdTdT-3’) 23 were obtained from Dharmacon (Lafayette, CO). Unlabeled negative control siRNA (siNC) and phosphatase and tensin homologue deleted on chromosome 10 (PTEN)-targeting siRNA (siPTEN) were purchased from Ambion (Foster City, CA) and Cell Signaling Technology (Danvers, MA), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Green fluorescent protein (GFP)-targeting siRNA (siGFP, sense: 5’-CAAGCUGACCCUGAAGUUdTdT-3’; antisense: 5’-GAACUUCAGGGUCAGCUUdTdT-3’) 22 and fluorophore-labeled negative control siRNA (siDY547, sense: 5’-DY547-UUCUCCGAACGUGUCACGUdTdT-3’; antisense: 5’-ACGUGACACGUUCGGAGAAdTdT-3’) 23 were obtained from Dharmacon (Lafayette, CO). Unlabeled negative control siRNA (siNC) and phosphatase and tensin homologue deleted on chromosome 10 (PTEN)-targeting siRNA (siPTEN) were purchased from Ambion (Foster City, CA) and Cell Signaling Technology (Danvers, MA), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we showed that this uptake can be visual ized by MRI (Figure 5a) and results in down regulation of the target gene (Figure 5b). 60 These studies lay the groundwork for future applications, in which genes that are implicated in islet graft loss (for example, those associated with allorejection, islet cell death and auto immune attack) can be similarly targeted to improve graft outcome. Furthermore, this approach enables non invasive tracking of the ironoxide conjugated siRNA and facilitates investigations of its relationship with graft fate.…”
Section: Manganese As An Agent For Islet Labelingmentioning
confidence: 98%
“…Constant transverse relaxivity (r2) at field strengths >0.5 T ■ 32 and high nanomolar sensitivity of detection 63 Proven clinical safety record ■ Can be used (through modifications of the nanoparticles' size and surface ■ coating) to detect and characterize specific cell subpopulations and/or biochemical processes 60,[64][65][66][67] Disadvantages:…”
Section: T2 Contrast Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The injection site of the pancreas was then sandwiched with a pair of tweezer-type electrodes, and electroporation was carried out using a square-pulse generator [24]. Magnetic nanoparticles comprising super-paramagnetic iron oxide and bearing short interfering RNA (siRNA) have been reported to transfect successfully siRNA into cultured pancreatic islet cells [59]. The internalization of magnetic nanoparticles into target cells is possible via manipulation of energy-dependent endocytosis [60,61].…”
Section: Gene Therapy Delivery Systems For the Treatment Of Diabetes mentioning
confidence: 99%